Ohmic contacts properties Pd/Ag metallization scheme on P-type GaN / C. W. Lim … [et al.] - Lim, C. W.; Yam, F.K.; Tan, C.K.; A., Abdul Aziz; Z., Hassan (2004)
In this work, we report on the characteristics of Pd/Ag metallization scheme deposited using thermal evaporation for the formation of ohmic contacts to p-type GaN. The electrical behavior and thermal stability at different annea1ing temperatures (400DC - 800DC) were: investigated. Specific contact resistivity using transmission Line Method (TLM) and current voltage (J-V) measurements were investigated. The minimum specific contact resistivity of 3.9 Qcm2 achieved after annealing at SOODC for 6 minutes. Changes in tile surface morphology off the contacts were observed using Scanning Electron Microscopy (SEM).